A next-generation sequencing study of arthropods in the diet of Laysan Teal Anas laysanensis - Holthuijzen, Wieteke A.; Antaky, Carmen C.; Flint, Elizabeth N.; Plissner, Jonathan H.; Wolf, Coral A.; Jones, Holly P. (Wildfowl, 2023)
The critically endangered Laysan Teal Anas laysanensis (known as koloa pōhaka in the Hawaiian language), in the Northwestern Hawaiian Islands has wild populations on Kamole (Laysan Island), Kuaihelani (Midway Atoll NWR) and Hōlanikū (Kure Atoll). The Laysan Teal face a new risk on Sand Island in Kuaihelani: non-target poisoning via a pending House Mouse Mus musculus eradication programme. After mice were observed attacking and depredating Laysan Albatross Phoebastria immutabilis (mōlī) in 2015, plans to eradicate the mice were developed to protect this seabird species. This approach, however, risks poisoning the Laysan Teal. To reduce exposure, teal will be translocated during mouse eradication. Even so, there remains a potential risk of secondary poisoning for teal by ingesting arthropods that feed on mouse bait. We therefore used next-generation sequencing (NGS) to identify which arthropods teal consume. From August 2019 to February 2020, we collected 71 fresh teal faecal samples on Sand Island, and successfully extracted DNA from 21 samples. Via NGS, we found that teal most frequently consumed cockroaches (order: Blattodea), freshwater ostracods (Cyprididae), midges (Chironomidae) and isopods (Porcellionidae). To a lesser degree, teal also ate spiders (Araneae), moths (Lepidoptera), beetles (Coleoptera), springtails (Entomobryomorpha), thrips (Thysanoptera) and crabs (Decapoda). Notably, the teal on Sand Island showed differences in diet from those on Kamole, which mainly eat flies (Diptera) and brine shrimp (Anostraca, Artemia sp.). Our study serves as a model for risk mitigation during invasive rodent eradication.